Pengaruh Kebijakan Pembelajaran Digital dan Professional Learning Community Terhadap Kualitas Pendidikan Melalui Kinerja Guru - Islami, Jundu Muhammad Mufakkirul; Sumarsono, Raden Bambang; Sunarni, Sunarni (Universitas Sarjanawiyata Tamansiswa, 2025)
This study aims to analyze the influence of digital learning policies and professional learning communities (PLC) on the quality of education, with teacher performance as a mediating variable. The research method used is quantitative with the Partial Least Square Structural Equation Modeling (PLS-SEM) approach. Data was collected through questionnaires from teachers at various levels of education and analyzed using SmartPLS 4.0 software. The results of the study show that digital learning policies and PLC have a significant effect on teacher performance and directly on the quality of education. In addition, teacher performance has proven to be a significant mediating variable in the relationship between digital policy and PLC on the quality of education. The structural model built has high explainability, with an R² of 0.844 for education quality and 0.762 for teacher performance. These findings affirm the importance of digital policy integration and strengthening PLC in improving the quality of education through the central role of teachers. The recommendations are directed at strengthening digital literacy, facilitating teacher professional collaboration, and improving the technology-based learning evaluation system.